2022
DOI: 10.3390/educsci12080561
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Student Performance in a Structural Analysis Course: Continuous Assessment before and after the COVID-19 Outbreak

Abstract: The COVID-19 pandemic situation in 2020 forced educational institutions worldwide to fully adopt online learning for both teaching and assessment. However, this change may lead to less satisfactory learning outcomes, if the online technologies used have not been adequately applied. This study compares student engagement and performance through online continuous assessment in a one-semester structural analysis course for undergraduate architecture students before and after the pandemic outbreak. Online continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…A possible explanation for this different behavior could be that during the COVID-19 lockdown, the University of Almería fixed a mandatory 50% of CA in all the courses; the marks in the CA part are significantly higher in e-learning teaching (50.51% for e-learning against 36.5% got in in-person taught courses) lowering the motivation for exam preparation in some students as have been reported in [10,14,23]. This rise in online CA was also reported by De Santos Berbel et al [54] but the authors also found a growth in the dropout rate, which could have a negative effect on the variable Exam because the student's withdrawal is recorded in this variable with zero. Another possible explanation could be that there is more room for cheating in online CA: instructors could have made a bigger effort to avoid cheating in the online final exam by, for example, increasing the bank of questions or setting a tight completion time whereas in blended teaching the final exam is face to face.…”
Section: Discussionsupporting
confidence: 63%
“…A possible explanation for this different behavior could be that during the COVID-19 lockdown, the University of Almería fixed a mandatory 50% of CA in all the courses; the marks in the CA part are significantly higher in e-learning teaching (50.51% for e-learning against 36.5% got in in-person taught courses) lowering the motivation for exam preparation in some students as have been reported in [10,14,23]. This rise in online CA was also reported by De Santos Berbel et al [54] but the authors also found a growth in the dropout rate, which could have a negative effect on the variable Exam because the student's withdrawal is recorded in this variable with zero. Another possible explanation could be that there is more room for cheating in online CA: instructors could have made a bigger effort to avoid cheating in the online final exam by, for example, increasing the bank of questions or setting a tight completion time whereas in blended teaching the final exam is face to face.…”
Section: Discussionsupporting
confidence: 63%
“…This course follows a blended-learning scheme with weekly assignments, both synchronous and asynchronous [18]. The final grade in the course consists of three grades.…”
Section: Methodsmentioning
confidence: 99%
“…Asynchronous learning systems are based on communication platforms that do not require timely engagement among the individuals involved in the educational process [17]. Based on students' evaluation results, previous studies have suggested that asynchronous assignments in blended learning can help to maintain the level of learning and consolidate knowledge, even in adverse conditions and under severe constraints [18][19][20][21][22]. Learning management platforms for distance learning facilitate interactions between participants using a framework known as 'request-response'.…”
Section: Blended Learningmentioning
confidence: 99%
“…These experiences have tremendous potential to influence students' self-confidence (Gill, 2015). Questions of how to ensure the quality of online learning and also how to provide an assessment of knowledge that truly reflects what students know have come to the forefront among practitioners (De Santos-Berbel, Hernando García, De Santos-Berbel, 2022). The reason for these questions and consequent discussions was the rapid transition from face-to-face instruction to online instruction that took place in a virtual classroom in a home environment.…”
Section: Literature Reviewmentioning
confidence: 99%